PENGARUH KUALITAS PRODUK, MEDIA SOSIAL, DAN REKOMENDASI KOMUNITAS TERHADAP KEPUTUSAN PEMBELIAN PRODUK OLAHRAGA TENIS PADA KOMUNITAS TENISTENISAN.ID DI KOTA BANDUNG - Rivaldy Hafiz Herdiansyah; Ani Surtiani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of tennis in Bandung has shown significant growth, along with the growth of amateur tennis communities such as TenisTenisan.id. This situation has driven a growing demand for tennis products, making understanding the factors influencing purchasing decisions crucial. This study aims to analyze the influence of product quality, social media, and community recommendations on purchasing decisions for tennis products among members of the TenisTenisan.id community in Bandung.